Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

(*) If cosec theta – sin theta = m, sec theta – cos theta = n then (m square n)^2/3 + (m . n square)^2/3 =

(*)
If cosec theta – sin theta = m, sec theta – cos theta = n then (m square n)^2/3 + (m . n square)^2/3 =

Grade:11

2 Answers

Nishant Vora IIT Patna
askIITians Faculty 2467 Points
6 years ago
Hello student, Please find the answer to your question below

cosec Ø – sinØ = m => cos2Ø/ sin Ø = m

secØ – cosØ = n => sin2Ø / cos Ø = n

therefore,
m2n = cos3Ø
mn2= sin3Ø

So (m2 n)^2/3 + (m . n 2)^2/3 = (cos3Ø)^2/3 + (cos3Ø)^2/3= 1
Ayush Kumar
17 Points
3 years ago
Answer is incorrect information on how to do it in the next few months ago I have a good time and consideration and hope to see you soon to discuss the possibility of working with the morning Google search rankings have dropped on Google and producing the morning to you as well as well at least one person can you please confirm that the

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free